Penyimpanan Audit Log Dengan Menggunakan Apache Kafka - Ardiansyah, Achmad (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Recently, there are many computer programs that being use for many purposes, so computer program will be entering complex programing era. If a system or a program become complex, it will need a new method to audit logs from the systems for an assurance if something is happening. For Example Error or Output that should not be happening  but found after it release. This experiment will be using Apache kafka as a tool to make sure the system is making an audit logs without interrupting the main process. After some experiment using some of test case scenario, the result is audit logs using kafka is simple to use and reliable, also this method will not interrupt the main process of the program